Clinical correlates of first episode schizophrenia-a comparative study - M., Kathir; K., Pugazhendhi; J., Ravishankar (International Journal of Research in Medical Sciences, 2018)
Background: Schizophrenia is a major mental disorder which has to be assessed early and managed actively even though long term functional outcome remains relatively poor. The aim of the study is to analyze negative symptoms, suicidal risk and substance use in first episode schizophrenics in comparison with multi-episode schizophrenics. Methods: 30 patients with drug naive first episode schizophrenia and 30 patients with multi episode schizophrenia, who attended the outpatient department of Psychiatry, Government Stanley Medical College, Chennai, Tamilnadu, India were studied to compare predisposing factors and spectrum of symptoms for Schizophrenia for a period of one year (January 2010-December 2010). Psychiatric questionnaire by Michael C. Hilton, DAST by Harvey A. Skinner, AUDIT by WHO, Suicide risk scale by National Health and Medical Research Council, PANSS by SR Kay were used to assess patients. Results: Unemployment and family history of suicide attempts were observed more in drug naive first episode schizophrenics. 90% of these patients had completed their primary education while 47% of multi-episode schizophrenics were illiterates. Positive symptoms (delusions, hallucinatory behaviour and suspiciousness) and negative symptoms (blunted affect, emotional withdrawal and social withdrawal) were observed more in first episode schizophrenics while PANSS, DAST, AUDIT scores did not find any differences between both the groups. Conclusions: In our study, the first episode schizophrenia patients were more educated, more unemployed and had more family history of suicide, elevated sub score of positive symptoms as measured by PANSS. Relative assessment of violence and serious behavior problems that are related to positive symptoms must be done and managed with anti psychotics.